La mort, l’oubli et les plaisirs - Anne Vega (Anthropologie & Santé)
This article looks at the origin of divergences between the norms conveyed by healthcare campaigns, the aspirations of hospital staff and those of patients with breast cancer. It is based on a qualitative study and highlights several differences which have rarely been the subject of research. The dominant discourse urging people to fight the pathology and remain calm fits poorly with the fluctuations in “morale” and with the exhaustion endured by the interviewees, whatever the evolution of their pathology might be. Furthermore, they react in accordance with their own life experience and most of them want to remain themselves “despite everything”. It is therefore vital for them to choose their support and to rediscover the pleasant sensations that they had enjoyed prior to the illness. The study thus underlines a paradox: it is the most “compliant” patients who have the greatest difficulty in appropriating the illness, in forgetting it, or in considering the possibility of death.